Unions and Investment in British Manufacturing Industry. - Denny, K; Nickell, S (1991)
This paper is concerned with the impact of unions on the investment rate in British industry. On the basis of an analysis of some 72 industries in the manufacturing sector, we find that, ceteris paribus, firms that recognize manual unions and have an average level of union density invest some 23 per cent less than firms that do not recognize unions. However, once we allow for union effects on wages and productivity, this overall effect is reduced to between 4 and 13 percent, depending on the degree of competition in the product market.